Parafunctional habits are associated cumulatively to painful temporomandibular disorders in adolescents - Fernandes, Giovana [UNESP]; Franco-Micheloni, Ana Lucia [UNESP]; Tesseroli de Siqueira, Jose Tadeu; Godoi Goncalves, Daniela Aparecida [UNESP]; Camparis, Cinara Maria [UNESP] (Sociedade Brasileira De Pesquisa Odontologica, 2016)
This cross-sectional study was designed to evaluate the effect of sleep bruxism, awake bruxism and parafunctional habits, both separately and cumulatively, on the likelihood of adolescents to present painful TMD. The study was conducted on a sample of 1,094 adolescents (aged 12-14). The presence of painful TMD was assessed using the Research Diagnostic Criteria for Temporomandibular Disorders, Axis I. Data on sleep bruxism, awake bruxism and parafunctional habits (nail/pen/pencil/lip/cheek biting, resting one's head on one's hand, and gum chewing) were researched by self-report. After adjusting for potential demographic confounders using logistic regression, each of the predictor variables (sleep bruxism, awake bruxism and parafunctional habits) was significantly associated with painful TMD. In addition, the odds for painful TMD were higher in the concomitant presence of two (OR=4.6, [95%CI=2.06, 10.37]) or three predictor (OR=13.7, [95%CI=5.72, 32.96]) variables. These findings indicate that the presence of concomitant muscle activities during sleep and awake bruxism and parafunctional habits increases the likelihood almost linearly of adolescents to present painful TMD.
Keywords: Adolescent; Bruxism; Pain; Temporomandibular Joint Disorders